Trade, Firms, and Wages: Theory and Evidence - Amiti, M.; Davis, D. R. (Review of Economic Studies, 2012)
How does trade liberalization affect wages? This is the first paper to consider in theory and data how the impact of final and intermediate input tariff cuts on workers' wages varies with the global engagement of their firm. Our model predicts that a fall in output tariffs lowers wages at import-competing firms, but boosts wages at exporting firms. Similarly, a fall in input tariffs raises wages at import-using firms relative to those at firms that only source locally. Using highly detailed Indonesian manufacturing census data for the period 1991 to 2000, we find considerable support for the model's predictions.